A new species of Diplocentrus (Arachnida: Scorpiones) from Oaxaca, Mexico - Santibáñez–López, Carlos E.; Francke, Oscar F. (Zootaxa, 2008)
Diplocentrus tenango sp. n. from the community of San Miguel Tenango in Southern Oaxaca is described. This is the eleventh species of the genus reported for Oaxaca. The tarsomere II spine formula is 5-6/6:6/6:7/7:7/7. Pectinal tooth counts are 12–13 in males, and 10–11 in females. It is clearly distinguished from its closest relatives: D. rectimanus Pocock 1898, and D. tehuano Francke 1977.